2017
DOI: 10.1177/0194599817701112
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety and Quality Improvement in Otolaryngology Education: A Systematic Review

Abstract: Objective The breadth and depth of patient safety/quality improvement (PS/QI) research dedicated to otolaryngology-head and neck surgery (OHNS) education remains unknown. This systematic review aims to define this scope and to identify knowledge gaps as well as potential areas of future study to improved PS/QI education and training in OHNS. Data Sources A computerized Ovid/Medline database search was conducted (January 1, 1965, to May 15, 2015). Similar computerized searches were conducted using Cochrane Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Now that education and experience in PSQI is mandated by the ACGME, otolaryngology faculty must determine how best to meet this requirement. A recent systematic review of PSQI education in otolaryngology demonstrated an increase in publications of PSQI projects related to resident education since 2008 . Interestingly, none of the articles in this series pertained to formally integrated curricula on the fundamentals of PSQI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Now that education and experience in PSQI is mandated by the ACGME, otolaryngology faculty must determine how best to meet this requirement. A recent systematic review of PSQI education in otolaryngology demonstrated an increase in publications of PSQI projects related to resident education since 2008 . Interestingly, none of the articles in this series pertained to formally integrated curricula on the fundamentals of PSQI.…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review of PSQI education in otolaryngology demonstrated an increase in publications of PSQI projects related to resident education since 2008. 29 Interestingly, none of the articles in this series pertained to formally integrated curricula on the fundamentals of PSQI. In fact, only a small number of the articles focused on integrating PSQI otolaryngology resident educational curricula.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) process 6,7 was previously published by our team 5 : An information specialist assisted in the development of subject headings outlined in Table I. Computerized Ovid/Medline, EMBASE, PubMed, and Cochrane database searches were performed from January 1, 1965, through September 30, 2019.…”
Section: Information Sources and Search Strategiesmentioning
confidence: 99%
“…Outcome variables were defined a priori and previously outlined in our education study. 5 In brief, associated study design information and otolaryngology subspecialty were recorded in the Excel (Microsoft Corp., Redmond, WA) database, version 2013. As the data was analyzed, broad focus areas were identified into which studies could be further categorized.…”
Section: Data Extraction and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation